The Law of Legitimacy: An Instrument of Procreative Power - Fellows, Mary Louise (Columbia Journal of Gender and Law, 1993)
The purpose of this Article is to explore how inheritance law, through its reliance on the laws regarding legitimacy, affects the construction of sexuality and procreative power in our society. The crucial importance of female monogamy in a private property regime is well-recognized. It is the only means by which a man can assure himself that his wealth will be inherited by his offspring. The enforcement of female monogamy by men enhances a man’s procreative power because it provides the basis for his claim of paternity.